Analysis of the content of the mathematics book for the fifth grade of primary school in the light of the criteria of integrative organization in the Kingdom of Saudi Arabia - Al-Shehri, Somayya Mohammad; Al-Salal, Mounira (Journal of Curriculum and Teaching Methodology, 2023)
The current study aimed to provide criteria for integrative organization that should be included in the content of the fifth-grade mathematics textbook. It also aimed to assess the extent to which the content of the fifth-grade mathematics textbook addresses integrative organization criteria. This was achieved using a descriptive methodology, where the researcher prepared a list of integrative organization criteria and constructed a content analysis card for the mathematics textbook. The study sample consisted of the mathematics textbook prescribed by the Ministry of Education for the fifth grade in the academic year 1439/1440 AH (first semester).The results revealed that the areas of integrative organization were included in the fifth-grade mathematics textbook to varying degrees. The content domain ranked first with a very high level of availability. On the other hand, the activities domain ranked last with a low level of availability. The objectives domain obtained a high
Keywords: integrated organization criteria; fifth-grade mathematics textbook; content analysis